Feminist Companion to Paul : Deutero-Pauline Writings. - Levine, Amy-Jill (Feminist companion to the New Testament and early Christian writings., 2003)
The seventh volume of this Companion series is devoted to the writings ascribed to Paul but widely thought not to be genuiinely from the Apostle. These are of particular importance in showing how Paul's authority was exploited in the Early Church, and the topics addressed often deal with Christian discipline and hierarchy. Hence there is a particularly strong feminist agenda to be explored here. The Pastoral Epistles, Ephesians and Colossians are prominent among the writings addressed in this sparkling collection, and the authors include David Scholer, Luise Schottroff, Bonnie Thurston, Lilian.